Knowledge Positions in Aotearoa and Turtle Island Art Museums - Eshraghi, Leuli; Ash-Milby, Kathleen; Nuku, Maia; Borell, Nigel (Artlink, 2020)
Art, performance, and spoken or now written text, all belong to the same register of cultural practice in the First Nations I am familiar with or belong to: ceremony. This ceremonial register takes place in a set of spaces created to enact cultural responsibilities to place, people and balance. Galleries and museums, as sites of cultural production and presentation, have the potential to nurture new ceremonies and new working methods.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hearts of our People: Native Women Artists - Ahlberg Yohe, Jill; Greeves, Teri (University of Washington Press, 2019)
"Women have long been the creative force behind Native American art, yet their individual contributions have been largely unrecognized, instead treated as anonymous representations of entire cultures. 'Hearts of Our People: Native Women Artists' explores the artistic achievements of Native women and establishes their rightful place in the art world. This lavishly illustrated book, a companion to the landmark exhibition, includes works of art from antiquity to the present, made in a variety of media from textiles and beadwork to video and digital arts. It showcases more than 115 artists from the United States and Canada, spanning over one thousand years, to reveal the ingenuity and innovation fthat have always been foundational to the art of Native women."--Page 4 de la couverture.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice LGBTQ+; 5-Créateur.rice autochtone; _Nettoyé

Archival Predecessors and Indigenous Modernisms: Archives in Contemporary Curatorial Practice on the Northwest Coast - Kisin, Eugenia (RACAR: revue d'art canadienne / Canadian Art Review, 2017)
Les projets d'expositions archivistiques—et leur documentation—sont des lieux de production de connaissances en histoire de l'art, ainsi que des interventions politiques, qui placent les documents dans un autre contexte afin d'interroger les canons et les façons de voir des colonialistes-colons. À partir de ces relations discursives, visuelles et archivistiques, cet article examine deux rétrospectives solos des œuvres sculptées et peintes des artistes modernistes kwakwaka'wakws, Doug Cranmer ('Namgis) et Henry Speck (Tlawit'sis), présentées à Vancouver en 2012. En considérant comment les conservateurs ont fait appel aux archives familiales intimes et à des documents du domaine public, il traite de l'utilité des archives du modernisme pour activer des liens affectifs, ancestraux et familiaux au-delà des modes de compréhension canoniques et historiques des mouvements esthétiques et des contextes de production
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

“Embodiment and Subjectivity”: Intersectional Black Feminist Curatorial Practices in Canada - Joachim, Joana (RACAR: revue d'art canadienne / Canadian Art Review, 2018)
Dans le contexte de l’héritage canadien de colonialisme et de profond racisme, les musées ont contribué à l’oppression des Noir.e.s, des communautés de couleur et des peuples autochtones en gardant le silence ou en supprimant certaines histoires sous prétexte d’« objectivité ». Cet article examine les pratiques commissariales de deux femmes noires canadiennes, Gaëtane Verna, directrice et conservatrice en chef de la galerie d’art contemporain The Power Plant, et Andrea Fatona, commissaire indépendante, afin de situer le commissariat critique à l’intérieur de perspectives afroféministes intersectionnelles. En conformité avec une base conceptuelle fondamentale de ce féminisme, je soutiens que ce qui rend l’acte commissarial « critique » est la reconnaissance non seulement de la position qu’une personne occupe dans la société, mais aussi de celles dont elle ne fait pas toujours l’expérience. En examinant les pratiques de ces deux femmes, je mets au jour une riche histoire de l’art et du commissariat des Noir.e.s au Canada.
Keywords: 1-Histoire de l'art; 2-Genre et sexualité; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice noir.e; 5-Autrice; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

Kwah í:ken tsi Iroquois - Rice, Ryan (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2008)
Catalogue d'exposition avec des textes de Ryan Rice, Françoise Charron, Emily Falvey et Hilda Nicholae.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Hochelaga revisité = Hochelaga revisited - Rice, Ryan (MAI (Montréal, arts interculturels), 2009)
Catalogue d'exposition avec des textes de Ryan Rice; Jason Baerg; Lori Blondeau; Martin Loft; Cathy Mattes; Nadia Myre; Ariel Lightningchild Smith.
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Art for a New Understanding: Native Voices, 1950s to Now - Hopkins, Candice; Well-Off-Man, Manuela; Besaw, Mindy N.; Crystal Bridges Museum of American Art (University of Arkansas Press, 2018)
"Art for a New Understanding, an exhibition from Crystal Bridges Museum of American Art that opened in October 2018, seeks to radically expand and reposition the narrative of American art since 1950 by charting a history of the development of contemporary Indigenous art from the United States and Canada, beginning when artists moved from more regionally-based conversations and practices to national and international contemporary art contexts. This accompanying book documents and expands on the histories and themes of this exciting exhibition. This fully illustrated volume includes essays by art historians and historians and reflections by the artists included in the collection. Also included are key contemporary writings--from the 1950s onward--by artists, scholars, and critics, investigating the themes of transculturalism and pan-Indian identity, traditional practices conducted in radically new ways, displacement, forced migration, shadow histories, the role of personal mythologies as a means to reimagine the future, and much more. As both a survey of the development of Indigenous art from the 1950s to the present and a consideration of Native artists within contemporary art more broadly, Art for a New Understanding expands the definition of American art and sets the tone for future considerations of the subject. It is an essential publication for any institution or individual with an interest in contemporary Native American art, and an invaluable resource in ongoing scholarly considerations of the American contemporary art landscape at large."
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sensible Objects: Colonialism, Museums, and Material Culture - Edwards, Elizabeth; Gosden, Chris; Phillips, Ruth B. (Wenner-Gren international symposium series, 2020)
Anthropologists of the senses have long argued that cultures differ in their sensory registers. This groundbreaking volume applies this idea to material culture and the social practices that endow objects with meanings in both colonial and postcolonial relationships. It challenges the privileged position of the sense of vision in the analysis of material culture. Contributors argue that vision can only be understood in relation to the other senses. In this they present another challenge to the assumed western five-sense model, and show how our understanding of material culture in both historical and contemporary contexts might be reconfigured if we consider the role of smell, taste, touch and sound, as well as sight, in making meanings about objects.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; _Nettoyé

Museum Pieces: Toward the Indigenization of Canadian Museums - Phillips, Ruth B. (Ruth Bliss) (McGill-Queen's/Beaverbrook Canadian Foundation studies in art history, 2011)
Ruth Phillips argues that these practices are "indigenous" not only because they originate in Aboriginal activism but because they draw on a distinctively Canadian preference for compromise and tolerance for ambiguity. Phillips dissects seminal exhibitions of Indigenous art to show how changes in display, curatorial voice, and authority stem from broad social, economic, and political forces outside the museum and moves beyond Canadian institutions and practices to discuss historically interrelated developments and exhibitions in the United States, Britain, Australia, and elsewhere. Drawing on forty years of experience as an art historian, curator, exhibition critic, and museum director, she emphasizes the complex and situated nature of the problems that face museums, introducing new perspectives on controversial exhibitions and moments of contestation. A manifesto that calls on us to re-imagine the museum as a place to embrace global interconnectedness, Museum Pieces emphasizes the transformative power of museum controversy and analyses shifting ideas about art, authenticity, and power in the modern museum.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

On Aboriginal Representation in the Gallery - Jessup, Lynda; Bagg, Shannon (Mercury series, 2002)
This book provides a glimpse of thirteenth-century life and death in a southern Ontario Iroquoian community. The renovation of a Toronto soccer field in 1997 resulted in the accidental discovery of an Iroquoian ossuary--a large pit containing the remains of at least 87 people. The pit was excavated and recorded, and the remains reburied in accordance with the wishes of the Six Nations Council of Oshweken. Scientific analyses of the bones resulted in a remarkably detailed demographic profile of the Moatfield people, along with indicators of their health and diet. The book reports these findings and includes a complete database of maps and profiles on an accompanying CD-ROM. Ronald F. Williamson is president of Archaeological Services Inc., Toronto. Susan Pfeiffer is professor of anthropology at the University of Toronto. Source: Publisher
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

D’Indigena à Sakahàn. Éléments de réflexion pour une affirmation autochtone dans l’art contemporain - Franco, Marie-Charlotte (Inter, 2016)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Àbadakone: feu continuel = continuous fire - Dickenson, Rachelle; Hill, Greg A.; Lalonde, Christine (Musée des beaux-arts du Canada, 2020)
Ce survol de l'art contemporain indigène, qui connut un succès retentissant dès son ouverture en novembre 2019, a été prolongé jusqu'au 4 octobre au Musée des beaux-arts du Canada. Àbadakone permet de découvrir des œuvres de plus de 70 artistes qui revendiquent leur appartenance à quelque 40 nations, ethnies et tribus de 16 pays, dont le Canada. Traitant des thèmes de la continuité, de l'activation et de l'interdépendance, Àbadakone explore la créativité, les préoccupations et la vitalité qui marquent l'art indigène de presque tous les continents. L'exposition est organisée par les conservateurs du Musée des beaux-arts du Canada Greg A. Hill, Christine Lalonde et Rachelle Dickenson, conseillés par les commissaires Candice Hopkins, Ariel Smith et Carla Taunton, ainsi que par une équipe d'experts du monde entier. .
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Beat Nation: Art, Hip Hop and Aboriginal Culture - Ritter, Kathleen; Willard, Tania (Vancouver Art Gallery, 2012)
Catalgoue d'exposition
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Indigena: Perspectives Autochtones Contemporaines - Martin, Lee-Ann; McMaster, Gerald (Musée canadien des civilisations, 1992)
Catlogue d'exposition avec plusieurs textes.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Perspectives photographiques sur l’autochtonie (1984-2011) - Guignard, Sophie (Captures, 2018)
Cet article s'intéresse aux diverses compréhensions de la notion d'autochtonie qui peuvent être mises au jour par l'étude du travail de photographes autochtones en Amérique du Nord. Pour cela, nous étudions deux brochures d'expositions collectives de photographes autochtones : Contemporary Native American Photography (1984), et Steeling the Gaze. Portraits by Aboriginal Artists (2011)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

L’art autochtone à l’aune du discours critique dans les revues spécialisées en arts visuels au Canada. Les cas de Sakah à n et de Beat Nation - Pageot, Edith-Anne (Muséologies, 2018)
This article offers a qualitative and quantitive analysis of the critical reception of two exhibitions, Sakahàn:International Indigenous Art (National Gallery of Canada, Ottawa 2013) and Beat Nation: Art, Hip-Hop and Aboriginial Culture (organised and circulated by the Vancouver Art Gallery, 2013-2014). The study treats articles which appeared between 2012 and 2015 in English and French visual-arts publications. The comparative analysis intends to highlight general trends, in order to identify challenges that contemporary Indigenous arts pose for art criticism. A review of the texts shows that all commentators, whether francophone or anglophone, indigenous or non-Indigenous, have welcomed these two exhibitions warmly. The discrepancy between the number of essays in French and those in English reflects the demographic weight of these two linguistic communities and the geographic distribution of First Nations in Canada. This will qualify, without denying, the hypothesis of Quebec's tardiness on the indigenous question. The authors largely recognize the necessity of initiating indigenization of the museum and emphasize the movement to internationalize contemporary indigenous art. Yet many commentators, particulary Indigenous people, dispute the efficacity of the concept of "strategic essentialism" put forward by the commissioners of the Sakahàn catalog. Despite both a real interest in these two major exhibitions and the quality of the commentary, in the end, for events of such a scale few texts have been published on the subject. The criteria for appreciation rooted in the institutional sociology of art endeavour to fully take into account the challenges posed by certain central aspects of the approach of several Indigenous creators, such as the intangible dimensions of their civic engagement, the dissolution of particular outside venues and the sisterhood of certain projects.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; _Nettoyé

Decolonize Me - Igloliorte, Heather; Loft, Steve; Croft, Brenda L. (Ottawa Art Gallery = Galerie d'art d'Ottawa, 2012)
Catalogue d'exposition avec des textes de Loft, Igloliorte et Croft. Galerie d'art d'Ottawa.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 4-Océanie (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

SakKijâjuk: Art and Craft from Nunatsiavut - Igloliorte, Heather; Broomfield, Jenna Joyce; Chaulk, Aimee; Lalonde, Christine; Pottle, Barry (Goose Lane Editions, 2017)
Nunatsiavut, the Inuit region of Canada that achieved self-government in 2005, produces art that is distinct within the world of Canadian and circumpolar Inuit art. The world's most southerly population of Inuit, the coastal people of Nunatsiavut have always lived both above and below the tree line, and Inuit artists and craftspeople from "Nunatsiavut have had access to a diverse range of Arctic and Subarctic flora and fauna, from which they have produced a stunningly diverse range of work. Artists from the territory have traditionally used stone and woods for carving; fur, hide, and sealskin for wearable art; and saltwater seagrass for basketry, as well as wool, metal, cloth, beads, and paper. In recent decades, they have produced work in a variety of contemporary art media, including painting, drawing, printmaking, photography, video, and ceramics, while also working with traditional materials in new and unexpected ways. SakKijâjuk: Art and Craft from Nunatsiavut is the first major publication on the art of the Labrador Inuit. Designed to accompany a major touring exhibition organized by The Rooms Provincial Art Gallery of St. John's, the book will feature more than 80 reproductions of work by 45 different artists, profiles of the featured artists, and a major essay on the art of Nunatsiavut by Heather Igloliorte. SakKijâjuk - "to be visible" in the Nunatsiavut dialect of Inuktitut - provides an opportunity for readers, collectors, art historians, and art aficionados from the South and the North will come into intimate contact with the distinctive, innovative, and always breathtaking work of the contemporary Inuit artists and craftspeople of Nunatsiavut
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

D'horizons et d'estuaires: entre mémoires et créations autochtones - Larivée, Camille; Eshrāghi, Léuli (Éditions Somme toute, 2020)
"D'horizons et d'estuaires. Entre mémoires et créations autochtones est une collection d'essais réunissant les voix de 16 artistes, commissaires, historien·ne·s de l'art et travailleur·se·s culturel·le·s autochtones, tant francophones qu'anglophones, œuvrant dans les territoires que l'on nomme Québec. Faisant suite à des expositions, des performances, des résidences d'artistes et des discussions mises en place lors du Projet Tiohtià:ke (2017-2019) du Collectif des commissaires autochtones, ces textes honorent les relations et les affinités qui sont au cœur de ces pratiques en arts visuels. Quelle place occupe actuellement les créations visuelles autochtones dans la société québécoise? Comment les créateur·trice·s imaginent-iels le futur de leurs expressions culturelles? Par la diversité des points de vue et les enjeux soulevés par ces écrits, ce livre pose des questions cruciales sur l'avenir des arts autochtones et ouvre la porte à des dialogues longtemps attendus au Québec qui, nous l'espérons, permettront de créer de réels changements positifs. Il est maintenant temps de plonger dans ces imaginaires collectifs éblouissants et de nager dans les eaux ondulantes de ces mémoires résilientes. Le texte est accompagné de 28 photographies d'œuvres d'artistes autochtones."-- Fourni par l'éditeur
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Du grenier à la forêt : le musée de l’immatériel - Paré, Sylvie (Recherches amérindiennes au Québec, 2003)
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; _Nettoyé

Le jardin en ville, le cas des Jardins éphémères à Québec. Stratégie marchande et critique postcoloniale - Pageot, Édith-Anne (Globe, 2012)
Cet article se penche sur la portée philosophique du projet intitulé Jardins éphémères, un ensemble de onze jardins temporaires réalisés dans le cadre des activités visant à célébrer le 400ₑ anniversaire de la fondation de la ville de Québec au cours de l’été 2008. L’organisation, les intentions et les principaux thèmes sous-jacents aux différents projets sont présentés dans leur ensemble. Le jardin intitulé « Wampum 400 », créé par deux artistes autochtones, Domingo Cisneros et Sonia Robertson Piekuakamilnu, fait l’objet d’un commentaire plus long. L’analyse montre que le projet Jardins éphémères dans son ensemble incarnait les principaux enjeux actuels du jardin en ville. Certains aspects reconduisaient la vision idéelle du jardin, d’autres satisfaisaient la logique touristique de l’événement et d’autres, enfin, développaient une position critique qui concerne la réappropriation d’un espace à usage collectif et, du coup, interrogeaient les fondements épistémologiques et ontologiques du « jardin ».
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

L'art dans tous ses territoires au jardin des Premières-Nations: regards sur l'immatériel dans les œuvres du Concours d'œuvre murale éphémère - Lauzon Chiasson, Gabrielle (Université de Montréal, 2019)
De 2003 à 2017, le jardin des Premières-Nations du Jardin botanique de Montréal a été le lieu d'exposition de 12 œuvres d'artistes autochtones dans le cadre du Concours d'œuvre murale éphémère lancé par Sylvie Paré. Ce mémoire rassemble l'ensemble de cette exposition afin d'en relever le discours général et les liens que les œuvres entretiennent entre elles, avec le Jardin et avec les territoires
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Unsettled Landscapes - Dees, Janet; Hofmann, Irene; Hopkins, Candice; Sanromán, Lucia (SITE Santa Fe, 2014)
Published by SITE Santa Fe on occasion of the inaugural SITElines Biennial, 'Unsettled Landscapes'. Unsettled Landscapes was curated by Janet Dees, Irene Hofmann, Candice Hopkins, and Lucía Sanromán. The exhibition, featuring 47 artists from 14 countries, looks at the urgencies, political conditions and historical narratives that inform the work of contemporary artists across the Americas--from Nunavut to Tierra del Fuego. Through three themes--landscape, territory, and trade--this exhibition expresses the interconnections among representations of the land, movement across the land, and economies and resources derived from the land."--Résumé de l'éditeur
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 4-Amérique centrale (lieu de production du savoir); 4-Amérique du Nord (lieu de production du savoir); 4-Amérique du Sud (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créatrice; 5-Identités diasporiques; _Nettoyé

Exposer, diffuser, faire entendre sa voix: présence de l'art contemporain autochtone au Québec entre 1967 et 2013 - De Lacroix, Pricile (Université du Québec à Montréal, 2017)
Ce mémoire se penche sur la diffusion de l'art contemporain autochtone au Québec de 1967 à 2013. Grâce à un corpus constitué de 640 expositions comprenant au moins un artiste des Premières Nations, métis ou inuit s'étant tenues quelque part dans la province à l'intérieur de ces 46 années, il a été possible de dresser un portrait global raisonné de ce qui s'est fait – ou ne s'est pas fait – concrètement, au-delà des a priori maintes fois reconduits. Il démontre, par exemple, que la décennie 1990 n'a pas été si « désertique » qu'il n'y parait, mais que la période 2000-2013, malgré son apparente vigueur, cache plusieurs dynamiques à l'œuvre au Québec rendant la reconnaissance et l'intégration des artistes autochtones dans le grand réseau des arts contemporains encore difficile. Ce mémoire apporte un éclairage sur le rôle marquant joué par les réseaux parallèles dans la diffusion de l'art contemporain autochtone, celui, parfois novateur, joué par les musées d'histoire et d'ethnographie ainsi que par les musées au sein même des communautés autochtones, puis la fermeture bien visible des institutions d'art du Québec jusqu'au milieu des années 2000. Il met également en lumière la présence de solitudes existantes au Québec, c'est-à-dire celle qui opère une division entre les artistes autochtones francophones et anglophones, favorisant grandement ces derniers, ainsi qu'entre artistes autochtones versus allochtones, les deux se mélangeant encore difficilement au sein des expositions. Enfin, ce mémoire permet de constater qu'en quatre décennies, le nombre d'artistes autochtones pratiquant de manière professionnelle au Québec n'a cessé d'augmenter, que Montréal s'est inscrite de plus en plus comme une métropole pouvant attirer des artistes autochtones de calibre national et international, que certaines régions du Québec, comme le Saguenay et l'Abitibi, ont, contrairement à d'autres, fait preuve d'une ouverture certaine face à l'art autochtone, mais également qu'il y a eu – et qu'il y a peut-être encore – une corrélation entre événements festifs et expositions accrues d'art contemporain autochtone, ce qui a tendance à le garder dans le domaine du folklore au Québec, et nuire véritablement à la reconnaissance des artistes professionnels.
Keywords: 1-Histoire de l'art; 2-Approches sociologiques; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Étude de la réception; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Baliser le territoire: a stake in the ground : Manifestation d'art contemporain autochtone - Myre, Nadia (Les Éditions Art Mûr, 2012)
Catalogue d'exposition. Du 14 janvier au 25 février 2012 à Art Mûr (Montréal. Titre : Baliser le territoire : Manifestation d’art contemporain autochtone / A Stake in the Ground: Contemporary Native Art Manifestation. Commissaire : Nadia Myre Sonny Assu, Jason Baerg, Carl Beam, Rebecca Belmore, Kevin Lee Burton, Hannah Claus, Bonnie Devine, Raymond Dupuis, Edgar Heap of Birds, Vanessa Dion Fletcher, Nicholas Galanin, Greg Hill, Robert Houle, Maria Hupfield, Rita Letendre, Glenna Matoush, Alan Michelson, Nadia Myre, Marianne Nicolson, Michael Patten, Arthur Renwick, Sonia Robertson, Greg Staats, Tania Willard, Will Wils
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé

Sakahàn: art indigène international - Hill, Greg A.; Lalonde, Christine.; Hopkins, Candice (Musée des beaux-arts du Canada, 2013)
Sakahàn' celebrates a growing international commitment to the collection, study and exhibition of indigenous art. Featuring more than 75 artists from around the world, this remarkable project places indigenous art squarely at the centre of contemporary art produced today.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Épistémologies autochtones; 3-Afrique (corpus analysé); 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Amérique du Sud (corpus analysé); 3-Asie (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice PANDC; 5-Créateur.rice autochtone; 5-Créateur.rice noir.e; 5-Créatrice; _Nettoyé

When Latin American Art Took a “Decolonial Turn” - Chilewich, Nika (Hyperallergic, 2018)
An exhibition at Mexico City's Museo Jumex argues that from 1960 and '85, artists across Latin America created a "decolonial" cultural history. However, the use of the term is largely unclear.
Keywords: 1-Histoire de l'art; 2-Muséologie critique; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice

Close Encounters: The Next 500 Years - Farrell Racette, Sherry. (Plug In Editions., 2011)
Catalogue d'exposition publié à l'occasion de l'exposition tenue au Plug In Institute of Contemporary Art, Urban Shaman Contemporary Aboriginal Art, et Winnipeg Art Gallery, du 22 janvier au 8 mai 2011. Now is the moment to reconfigure our notions of time to reveal alternative ways of thinking and being for the future. In Close Encounters: The Next 500 Years Indigenous artists imagine the future within the context of present experiences and past histories. By radically reconsidering encounter narratives between native and non-native people, Indigenous prophecies, possible utopias and apocalypses, this exhibition proposes intriguing possibilities for the next 500 years. "We all in different measure have carved out the future," observes Hopi photographer and filmmaker, Victor Masayesva, in his book Husk of Time. "We are all clairvoyants, soothsayers, prophets, knowingly assuming our predictions. Close Encounters brings together over 30 Indigenous artists from across Canada, the United States, South America, Europe, Australia and New Zealand, including newly commissioned work from Rebecca Belmore, Faye HeavyShield, Kent Monkman, and Edward Poitras. Jimmie Durham's sculptural work A Pole to Mark the Centre of the World (at Winnipeg) will be an ongoing critique of widely held ideas surrounding space and location, while James Luna's poignant installation The Spirits of Virtue and Evil Await my Ascension, addresses issues of ritual and the passing of time. Close Encounters showcases artists and artworks that collectively invent provocative futures from a diversity of perspectives and practices. With its myriad histories, trajectories, tensions, collisions, and self-image(s), the city of Winnipeg offers an intriguing juxtaposition for these artistic mediations. Close Encounters: The Next 500 Years presents international Indigenous perspectives in a city that in many ways also epitomizes the future of Aboriginal people in Canada. Works in multiple venues throughout the city will serve as catalysts to invent different ways of thinking, acting, and being in the world of our shared future. At this pivotal moment in time, Close Encounters invites engagement with the speculative, the prophetic, and the unknown
Keywords: 1-Histoire de l'art; 2-Histoire/Historiographie critique; 2-Muséologie critique; 2-Épistémologies autochtones; 3-Amérique centrale (corpus analysé); 3-Amérique du Nord (corpus analysé); 3-Europe (corpus analysé); 3-Océanie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice autochtone; 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé